Strengths and Challenges of Counseling Professionals in Serving Trans Students in Daytime Secondary School - Alí Chaves-Jiménez (Revista Costarricense de Orientación, 2025)
Objective: The results of the fourth objective of the research on the care of transgender adolescents in secondary school are presented. This objective seeks to identify the main strengths and challenges of the Counseling professional in caring for transgender students.